2016
DOI: 10.1039/c6nr03698h
|View full text |Cite
|
Sign up to set email alerts
|

Novel Au- and Ge-based two-dimensional materials formed through topotactic transitions of AlB2-like structures

Abstract: The topotactic reaction of a layered compound, for example CaGe2, with HCl solution is a common and facile method to produce two-dimensional (2D) materials. In this work we demonstrate with first-principles calculations that this technique can potentially lead to a whole new family of 2D materials starting from three-dimensional crystals with AlB2-like structures. As representative cases, we show here that the de-intercalation of Sc and Ca atoms from ScAuGe and Ca2AuGe3 crystals is strongly exothermic and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This configuration is in agreement with experimental studies [45] [47] to be the same as that of Ca 2 AgSi 3 . In the recent DFT study [40], it was shown that the topotactic transformation of Ca 2 AuGe 3 can lead to the 2D material with composition AuGe 3 H 3 . With respect to electronic properties, both Ca 2 AgSi 3 and Ca 2 AuGe 3 are metallic.…”
Section: Ca 2 Agsi 3 Ca 2 Augementioning
confidence: 99%
See 1 more Smart Citation
“…This configuration is in agreement with experimental studies [45] [47] to be the same as that of Ca 2 AgSi 3 . In the recent DFT study [40], it was shown that the topotactic transformation of Ca 2 AuGe 3 can lead to the 2D material with composition AuGe 3 H 3 . With respect to electronic properties, both Ca 2 AgSi 3 and Ca 2 AuGe 3 are metallic.…”
Section: Ca 2 Agsi 3 Ca 2 Augementioning
confidence: 99%
“…In particular, when CaSi 2 (and likewise [37] for CaGe 2 ) crystals react with a solution of HCl acid [32], Ca atoms are removed and H atoms (or OH groups) are attached to the silicene layer to produce the wide-band gap semiconductor silicane (or siloxene). In a recent study [40], we showed with firstprinciples calculations that similar reactions (termed topotactic transitions or transformations) can be used to prepare Au-and Ge-based two-dimensional materials from the AlB 2 -like crystals of ScAuGe and Ca 2 AuGe 3 . In fact, the same approach can prepare a whole new family of 2D systems, a realization that serves as the main motivation to study the structural and electronic properties of the corresponding three-dimensional precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Recently, investigations of DMS have mainly focused on III-V, IV, II-VI, oxide and sulde semiconductors, such as GaAs, GaN, Si, Ge, ZnO, MoS 2 , etc. [9][10][11][12][13] The preparation of DMS mainly uses transition metal atoms or rare earth ions, which have spin magnetic moment, doped to substitute some atoms in the semiconductor material. [14][15][16] The magnetic moment of DMS is produced by the exchange of p state electrons of the anions and d state electrons of the magnetic ions, which are changed by the external temperature and doping concentration, so they may be ferromagnetic, sub ferromagnetic and antimagnetic.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2 Ge is a novel semiconductor material whose crystal structure and photoelectric properties are similar to Ca 2 Si [1,2]. With respect to Si, Ge has larger charge carrier mobility, a smaller dielectric constant and a larger excitation radius (Ge-24.3 nm, Si-4.9 nm), and hence a stronger quantum size effect [3,4]; Furthermore, Ca 2 Ge is compatible with the conventional Si processes and overcomes the physical quantum limitations of Si (conventional Si integrated circuit IC in the range * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%